2023
DOI: 10.1136/tc-2022-057710
|View full text |Cite
|
Sign up to set email alerts
|

Interest in quitting e-cigarette use by device type and smoking history in US adults

Abstract: BackgroundThe use of e-cigarettes has been increasing, especially since the introduction of ‘pod’ devices to the marketplace since 2018. Most adults who vape report interest in quitting. The present study examined level of interest in e-cigarette cessation between users with varying cigarette smoking histories and device types.MethodsData obtained from wave 5 (2018–2019) of the Population Assessment of Tobacco and Health study (n=34 309). Analyses were conducted on adult current established e-cigarette users, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Cessation 2024;10(June):26 https://doi.org/10.18332/tpc/189924 of tanks compared to disposable devices may indicate that individuals investing in these devices are more committed to quitting smoking and more likely to use them consistently 21 . However, it is important to note that a study suggests that people using disposable devices had higher odds of reporting a past-year quit attempt than people using tanks 22 . Further research is necessary to ascertain the reasons behind these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Cessation 2024;10(June):26 https://doi.org/10.18332/tpc/189924 of tanks compared to disposable devices may indicate that individuals investing in these devices are more committed to quitting smoking and more likely to use them consistently 21 . However, it is important to note that a study suggests that people using disposable devices had higher odds of reporting a past-year quit attempt than people using tanks 22 . Further research is necessary to ascertain the reasons behind these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 56% exclusively vaped nicotine 1 and were at high risk for transitioning to combustible tobacco product use, 2 or co‐using with other substances – particularly alcohol and cannabis – that could lead to worse health consequences 3,4 . A recent national survey showed that although 68% of adults in the U.S. who currently use e‐cigarettes plan to ever quit, only 17% tried to quit in the past year, 5 which was much lower than the 50% among adult cigarette smokers who made a quit attempt in the past year 6 . When people do try to quit vaping, a recent systematic review 7 indicated that most e‐cigarette users who made quit attempts reported quitting “cold turkey” (ie, quitting unassisted and without pharmacotherapy).…”
Section: Introductionmentioning
confidence: 99%